Neuropsychological Assessment Battery-Screening Module (S-NAB): Performance in treatment-seeking cocaine users. (November 2014) - Cannizzaro, Daniela L.; Elliott, Jennifer C.; Stohl, Malka; Hasin, Deborah S.; Aharonovich, Efrat
Abstract Background: Cocaine use is associated with cognitive impairments, which can have a negative effect on treatment retention and drug use. Thus, there is an increasing demand for a screening cognitive battery can be used by clinicians to detect such impairments in cocaine patients so that treatment can be adapted to patients' specific cognitive strengths and deficits. The Neuropsychological Assessment Battery-Screening Module (S-NAB) test for adults takes approximately 35–45 min to administer, and assesses attention, language, memory (verbal and visual), visual spatial reasoning, and executive functioning. Objective: The purpose of this descriptive study was to present S-NAB score results for a sample of treatment seeking adult cocaine users to determine its potential utility for detecting cognitive impairments in this population. Methods: In the present sample, 145 adult cocaine users participated in screening to enroll in an intervention to decrease cocaine use (59% male; 73.1% African American); screening included the S-NAB and self-report questionnaires. Results: A substantial proportion of the sample (44%) met criteria for impairment, i.e. composite scores of one or more standard deviations below the mean. Furthermore, memory scores were significantly lower than language and spatial scores (p < 0.007). Conclusions: The impairments detected by the S-NAB were generally consistent with those previously observed in samples of cocaine users completing other batteries, as well in other substance abusing samples completing the S-NAB. This suggests that the S-NAB can be considered an additional appropriate battery, as an alternative to other existing batteries, for assessment of the cognitive functioning of adult cocaine users.